Comprehensive modelling on various solar photovoltaic technologies based on local climate conditions: the potential, limitations and economic impact - Huam, Edbert Jun Ping (2022)
Solar Photovoltaic is a type of renewable energy technology that converts solar energy into electrical energy. This type of electricity generation does not produce any carbon dioxide (CO2) towards the surroundings as compared to burning of fossil fuels. He nce, this technology is a clean and environmentally friendly. However, not all solar power plant project is successful as it may prone to lack of planning, design, estimation and financial that will lead to failure operation of solar power plants. Since Ma county situated at the equator, where abundant of solar is available laysia is a . In order to fully utilize the solar energy, it is recommended to install the solar panel with tilted angle to obtain the maximum solar irradiation, while able to generate inc ome and electricity. The aim and objective in this project consist of computation modelling of python programming using the metrological data of the local climate, where the annual average solar irradiation, optimum tilt angle, orientation of solar pane l maximum solar irradiation received in a year. Next, and the in a specific area of land, the amount of carbon dioxide emission due to deforestation will be compared with the carbon dioxide avoidance due to installation of solar panel . This is to estimate whether the area of land is suitable for solar panel installation in order to introduce more renewable energy than fossil fuels. If the carbon dioxide emission is more than carbon dioxide avoidance, that area of land is not recommended for installation and should be left untouched. Lastly, the investment cost and annual income generated by the solar farm is estimated, while calculating the estimated payback period of the project. For the accuracy of simulation in estimating the tilt angle and orientation angle, the simulated results are compared with the literature review results and found out the overall accuracy is 66.67% , which is above average and accept able . In addition, the percentage error obtained between the solar irradiation received is within t 1he range of 2% error, which is acceptable. Next, the carbon dioxide presence and carbon dioxide avoidance are highly dependent on the area of clearance, local climate and electricity generated. The overall solar sites are able to avoid the carbon dioxide when it is operating. Lastly, the investment cost, annual income and payback period for specific solar sites are estimated as it will depends on the local interest rate and inflation rate.